Design of CMOS front-end receiver for wideband optical communication systems - Chen, Dandan (2012)
In the current wireless indoor communication market, Bluetooth is the dominating technology used. The main purpose of Bluetooth is to eliminate the need of cables interconnecting electronic devices. Operates at a range of 10 meters with the top data rate of 24 Mpbs, the use of Bluetooth in terms of high speed data communication is however, limited.